Axiological Dimension of Citizenship and Patriotism in a Worldview of Kazakhs: A Psycholinguistic Study - Kuzembayeva, Gulzhana (Lesya Ukrainka Eastern European National University, 2023)
Restoration of cultural heritage, revival of national traditions and basic elements of culture, reassessment of core and cultural values is of utmost importance in any human culture. In the context of present global developments enriching the dimensions of citizenship and reduced patriotism, this study aims at defining the values of citizenship and patriotism as perceived by the representatives of the Kazakh language and culture. The study manipulated ranking of the citizenship and patriotism values among the Kazakhs representing different gender categories, age groups and regions of Kazakhstan. The Mann-Whitney U-test and the Kruskal-Wallis test were employed to measure the variance among various groups of respondents. A word association test was conducted on the stimulus words Отан / homeland, отансүйгіштік / patriotism, тарих / history, тәуелсіздік / independence, еркіндік / freedom. Based on the received data, the association fields of the values of citizenship and patriotism were modelled and the semantic gestalts were defined. The ranking of values of citizenship and patriotism showed that the highly ranked value among all respondents, across both gender categories, all age groups (except 70+ years), and regions in Kazakhstan (except East Kazakhstan) was ‘independence’ (ranging from 4.76 to 4.84). The least ranked value among the representatives of the Kazakh language and culture except age groups of 50-70 years and 70+ years and South Kazakhstan region was ‘patriotism’. The word association test demonstrated that the values of citizenship and patriotism in the Kazakh language consciousness imply love for the birthplace and country, where a family and close people live, appreciation of courage of national heroes fighting for freedom and peace, value, happiness, and pride, offering bright future and opportunities.
Keywords: word association test; conceptualization of values; language consciousness; Kazakh language and culture bearers; citizenship and patriotism